Administering and analyzing the community needs assessment required for the Dallas Area Agency on Aging - Marstall, Kendra (My University, 2024)
I completed my Applied Practicum Experience at the Community Council of Greater Dallas, specifically with the Dallas Area Agency on Aging (DAAA) in Dallas, Texas. During this time, I supported the team in various formats. My primary responsibility was administering and analyzing the community needs assessment required for the submission of the agency’s Area Plan to state for government funding. I helped distribute the survey at a variety of community events and over the phone. Additionally, I completed data entry of over 500 surveys, and performed part of the data analysis for the final plan submitted to the state. I tabled at the annual DART Information and Health Fair held in May in celebration of Older Americans Month and worked in the community by visiting retirement communities and senior centers. During these visits, I would discuss services offered through the agency and distribute educational pamphlets. I also participated in delivering the National Diabetes Prevention Program alongside a trained staff member to seniors in the community. Topics discussed included the benefits of balanced diet, regular physical activity, and tips on how to establish healthy habits. I aided my preceptor in case organization, delivery of services, and administration of agency assessments. I also attended site visits alongside my preceptor. Lastly, I performed a retroactive analysis of caregiver coping mechanisms for stress. The final report from the analysis was submitted as an abstract to the annual Texas Public Health Association Conference, and it was accepted for an oral presentation. I worked in a collaborative environment and gained skills in communication, leadership, ethics, data analysis, service delivery, and health education.
Keywords: Physical activity; Long-term care; Rural; Aging; Facilitators and barriers